Pengaruh Orientasi Pasar dan Orientasi Kewirausahaan Terhadap Keunggulan Bersaing Melalui Inovasi Produk sebagai Variabel Antara (Studi Kasus pada IKM Batik di Kampung Batik Laweyan, Solo) - Renita Helia; Naili Farida; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated by competition between batik industries increasingly stringent. Kampung Laweyan Solo is one of small and medium sized enterprises that compete with others. Not only compete with domestic batik industries but also compete with international batik industries. To compete with others, batik industries should create superiority in their products. So that, SMEs in Kampung Laweyan Solo should have a competitive advantage to compete with others. Innovation can be used as one of the strategies to achieve competitive advantage. Therefore, product innovation must be improved to achieve competitive advantage by way of market oriented and entrepreneurial oriented.Type of research is explanatory research, whose aim is to examine the causal relationship between competitive advantage, market orientation, entrepreneurial orientation and product innovation. The population of about 124 owners of batik industries in Kampung Batik Laweyan, Solo. The sampling technique used was purposive sampling so that the number of sample are 50 people. The analysis technique used was quantitative analysis with SPSS (Statistical Package For Social Science) as a tool. The results showed that the effect of partially or simultaneously between market orientation, entrepreneurial orientation and product innovation  on competitive advantage. Based on the results of path analysis (path) shows that product innovation is the intervening variable.